Analysis of Cymbopogon Citratus, Pinus sylvestris and Syzygium cumini biodiesel feedstocks for its fatty acid composition. (2021) - Bhaskar, K.; Sassykova, L.R.; Prabhahar, M.; Shebha Percis, E.; Nalini, A.; Jenish, T.; Jayarajan, J.; Sendilvelan, S.
Abstract: Rapid depletion of fossil fuel and increased demand for petroleum products in energy and transportation sector motivated the researchers to find a substitution for petroleum diesel. Biodiesel is one among the alternate to this crisis. Biodiesel is a combined mixture of fatty acid alkyl esters obtained by the reaction of triglycerides of vegetable or animal origin with alcohol in the presence of a catalyst. The fatty acid profile influences the overall properties of the biodiesel. The properties of individual fatty acid depend on the occurrence of double bonds, fatty acid chain length and branching. Better understanding of the fatty acid composition and correlating the fuel properties is of utmost importance in improving the optimal performance. In the present study, feedstocks of Cymbopogon citratus, Pinus sylvestris and Syzygium cumini is analysed for its fatty acid composition study using Gas Chromatography assisted with mass spectrometry. Based on GC–MS Analysis, fifteen types of fatty acids in Cymbopogon citratus, Pinus sylvestris and Syzygium cumini oil methyl esters were analysed and defined; all these esters are amalgamations of saturated and unsaturated fatty acids. The variation in fatty acid compositions affects the properties of the esters. GC–MS synthesis showed that methyl, ethyl esters free from dirt for the three feedstocks. Few impurities like mainly mono-, di- and triglycerides were found.